Seed Bundle Training Report - Chikoye, David; Sibeso, Consent (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
In collaboration with the National Smallholder Farmers Association of Zambia (NASFA), the Seed Bundle of AICCRA recently trained 280 youth in Chikankata, Mumbwa, Kapiri Mposhi, Chongwe, and Mkushi Districts of Zambia. The training focused on soybean seed production and agribusiness management, with an aim to equip young farmers with critical skills in both technical and business areas, fostering resilience and economic sustainability in agribusiness.